Minat Beli Ulang (Winback) Program Bpjs Ketenagakerjaan Bagi Peserta Yang Telah Klaim Jht - Trisnal Trisnal; Siti Jahroh; Heny Kuswanti Suwarsinah (Jurnal Ilmiah Global Education, 2026)
BPJS Ketenagakerjaan (Employment Social Security Agency) is a social security institution that administers the JKK, JKM, JHT, JP, and JKP programs under Law No. 24 of 2011. The number of registered participants increased from 54.97 million (2019) to 61.08 million (2023), but the number of inactive participants remains high, at 19.5 million per year. JHT claims from 2019–2023 reached 14,340,989 cases, significantly higher than those for JKK and JKM, making it a potential target for winback strategies. However, the post-claim reactivation rate for JHT remains low. At the Mandailing Natal Branch Office, from January 2024–September 2025, only 306 of 5,702 claimants (5.3%) reactivated. This study uses the Extended Theory of Planned Behavior (E-TPB) by adding perceived benefits and perceived risks to analyze repurchase intention. The quantitative survey method was applied using SEM-PLS analysis (SmartPLS 4). The results showed that subjective norms had the strongest influence on winback interest, followed by perceived benefits and perceived behavioral control. Conversely, attitudes toward the behavior and perceived risks were insignificant. These findings confirm that winback decisions are more influenced by social factors, belief in benefits, and ease of the reactivation process. Community-based strategies and service simplification are key to increasing participant sustainability.